Variation in predation regime drives sex‐specific differences in mosquitofish foraging behaviour. Issue 5 (16th March 2021) - Pärssinen, Varpu; Hulthén, Kaj; Brönmark, Christer; Björnerås, Caroline; Ekelund Ugge, Gustaf; Gollnisch, Raphael; Hansson, Lars‐Anders; Herzog, Simon David; Hu, Nan; Johansson, Emma; Lee, Marcus; Rengefors, Karin; et al.
Abstract : Predation is a well‐studied driver of ecological selection on prey traits, which frequently drives divergence in anti‐predator performance across environments that vary in predation risk. However, predation also alters prey mortality regimes, where low predation risk often results in higher prey densities and consequently higher intensities of intraspecific resource competition. In addition, predation risk alters the foraging context, as acquiring food can be risky in the presence of predators. Thus, different predation regimes can drive divergent selection on traits associated with resource competition, such as foraging behaviours. Moreover, because sexes often differ in susceptibility to predation and limitations to their reproductive output, the intensity of the tradeoff between predator avoidance and resource competition may depend on sex. We used a laboratory experiment to assess key aspects of foraging performance in a predator‐free context in Bahamas mosquitofish Gambusia hubbsi wild‐caught from multiple populations that experience either high or low levels of predation risk. When competing for limited food resources at a common density, females from low‐predation regimes showed higher foraging and food consumption rates than females from high‐predation regimes. Males showed fewer differences between predation regimes, and an opposite pattern from females. We suggest these sex‐specific effects result from females facing a greater tradeoff between predation risk and resource competition, combined with males from high‐predation environments elevating foraging behaviours in the absence of nearby predators and females. Females of this species are larger than males, bear live young and show higher foraging rates in the wild than males. On the other hand, males spend more time pursuing females in the wild, and may exhibit greater flexibility in foraging behaviours based on the immediate context. Our results show that varying levels of predation risk can lead to differences in behaviours associated with resource competition, but these effects can strongly differ between sexes.